Al-Ma‘had al-Turāthī wa al-Ta’hīl al- Mihanī:Tajribah Nūr al-Jadīd al-Tawaqu‘i al-Mustaqbal - Murodi, Murodi; Wahid, Hamid. W (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1998)
This paper will discuss the characteristics of pesantren education in relation to vocational education, background and objectives by taking the case of boarding Nurul Jadid, Karanganyar, Paiton, Probolinggo, East Java.Unlike what Abdurrahman Wahid once argues, since the 1970's, the pesantren, traditional Islamic boarding schools, have not been construed as unique and closed institution, but have become cultural institution actively responding to social changes. Recently pesantren have had no choice but to open their doors to the DOI: 10.15408/sdi.v5i2.755